Analisis Dakwah Kh. Mustofa Bisri Dalam Konteks Masyarakat Modern - Hadi, Moch Alfin; widadi, Widadi; Zuhriyah, Luluk Fikri (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2025)
Da’wah as an instrument of socio religious tranformation, plays a strategic role in shaping public ethics, thought patterns, and communal character. KH. Ahmad Mustofa Bisri, a prominent Indonesian Muslim scholar, poet and cultural figure, stands out as a central figure in promoting moderate Islam in Indonesian. This study aims to identify, analyze, and contextualize the methods and focus of KH. Mustofa Bisri da’wah within the framework of modern, pluralistic society. Using a descriptive qualitative approach and literature review as the primary technique, the study reveals tha KH. Mustofa Bisri employ a humanistic, aesthetic, contextual, and spiritually reflective approach to da’wah. His methods include dialogical and empathetic preaching, inclusive aducational practices, the use of social media, religious literature and poetry, as well as the integration of Islamic values with artistic expression. The focus of this da’wah extends beyond ritual observance, emphasizing religious consciouness, interfaith tolerance, moderate theology, social critique through non provocative language, and intellectual ampowerment of the youth. His soft spoken, inclusive communication style proves effective in promoting an understanding of Islam as a peaceful, substantial, and humanistic faith. In conclusion, KH. Mustofa Bisri da’wah model offers a strategic paradigm for contemporary Islamic propagation one that is relevant to the challenges of the modern age and rooted in the values of peace, justice and human dignity.